Comparison of Attenuation of Hemodynamic Response to Laryngoscopy with Nalbuphine versus Fentanyl in Patients undergoing Laparoscopic Cholecystectomy - Kainat, Mahendar, Udesh Kumar, Gotam Kumar, Maham Anwar, Mehreen Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the hemodynamic response in laryngoscopy with fentanyl versus nalbuphine in patients undergoing laparoscopic cholecystectomy. Study Design: Randomized controlled trial. Place and Duration of Study: Department of Anesthesiology, Surgical Intensive Care and Pain management, Dow University of Health and Science, Dr. Ruth K.M. PFAU, Civil Hospital Karachi from 17th July 2020 to 16th January 2021. Methodology: Sixty patients between the age of 20-60 years of both genders falling under ASA Class-I and II undergoing laparoscopic cholecystectomy for cholelithiasis which were randomly allocated into two treatment groups. Patients in Group A received fentanyl while Group B was given nalbuphine before endotracheal intubation. Outcome variables were mean heart rate and mean diastolic and systolic blood pressure measured 15 minutes after intubation. Results: The mean age was 41.7±11.9 years. There were 21 (35.0%) male and 39 (65.0%) female patients. Mean body mass index was 25.5±2.6 kg/m2. Thirty five (58.3%) patients belonged to ASA Class-I while 25 (41.7%) patients belonged to ASA class-II. There was no statistically significant difference between fentanyl and nalbuphine in terms of mean heart rate 15 minutes after intubation (87.37±3.30vs. 86.33±4.23 bpm; p-value=0.296). However, the mean diastolic (73.23±3.77 vs 81.40±4.79 mmHg; p<0.001) and systolic (117.30±4.21 vs 121.53±4.75 mmHg) hypotension was observed in fentanyl group as compared to nalbuphine group. Conclusion: Intravenous fentanyl infusion significantly attenuated the hemodynamic response to tracheal intubation in terms of significantly lower mean diastolic and systolic blood pressure as compared to conventional practice of nalbuphine which is desirable in patients undergoing general anesthesia. Keywords: Endotracheal intubation, Hemodynamic response, Fentanyl, Nalbuphine